Short-Run Productivity Behavior in U.S. Manufacturing - Wilson, Thomas A.; Eckstein, Otto (The Review of Economics and Statistics, 1964)
IN recent years the behavior of productivity has received increasing theoretical and empirical attention. Two basic approaches have been developed. The first focuses upon the long-run trend in output per man-hour and examines the sources of that trend. The second focuses upon the short-run or cyclical behavior of productivity. The purpose of this paper is to explain the characteristic behavior of output per man-hour over the business cycle and to identify changes in the cyclical response mechanism. An explanation of cyclical changes in productivity is essential for an analysis of unit labor costs, and is therefore a necessary ingredient in an explanation of the price level and its movements. It is also a necessary precondition to understanding the longer-run trends; cyclical fluctuations in output per man-hour are large, and the trends based on capital and technology cannot be seen until the short-run variations have been removed.